The Interpretation of (daughter Zion): An Approach of Cognitive Theories of Metaphor - Kim, Hyukki (My University, 2006)
The metaphor (daughter Zion) is examined using cognitive theories of metaphor which consider a metaphor not to be an exceptional matter of poetic creativity or excessive rhetoric, but to be an ordinary component of everyday language and its effect to be mainly dependent on its cultural context.
The metaphor "daughter Zion" signifies the Israelites' pride and faith in relationship with God. Threatened by a mighty enemy, biblical writers express their confidence in God by using "daughter Zion." They also warn the sinful Israelites using the image of daughter Zion's pain and killing. After Israel 's destruction, they reveal their lament and distress in the picture of daughter Zion's ruin. However, "daughter Zion" is also a metaphor of hope. Daughter Zion's restoration symbolizes the restoration of her people. Therefore, the biblical writers, who warn Israelites using the picture of daughter Zion's ruin, encourage them to have hope by employing daughter Zion.
Keywords: Religion; Religion